التنزيل في قانون الأسرة الجزائري وحكمه في الشريعة الإسلامية - عرباوي, الحاج علي (University of Eloued جامعة الوادي, 2020)
ملخص لقد حرص الإسلام على مبدأ العدل في توزيع الثروة وإعطاء كل ذي حق حقه، ولعل من أكثر الأبواب الفقهية عناية بذلك باب الميراث والوصايا، وقد وردت فيه آيات قرآنية وأحاديث نبوية محكمة حتى لا يحصل تنازع بين المسلمين، وقد استجد في هذا العصر نظام جديد له علاقة بالوصايا والمواريث، وهو ما يسمى بالتنزيل أو الوصية الواجبة، الغرض منه إعطاء الحفدة من مال مورثهم حالة موت الأب في حياة أبيه ويترك أولاده صغارا فقراء محتاجين ثم يموت الجد ويأخذ أعمامهم الميراث كله، ويبقى هؤلاء الأحفاد فقراء، في حين أن أباهم لو كان حياً لكان له نصيب من الميراث، وهو ما أخذ به قانون الأسرة الجزائري بعد سنة 1984، ووقع فيه خلاف ونقاش في تكييفه من الناحية الشرعية، ثم بعد ذلك الحكم عليه، فأردت من خلال هذا البحث الكشف عن حقيقته وحكمه في الشريعة الإسلامية. -------------------------------------------- Abstract Islam has been keen on the principle of justice in the distribution of wealth and to give everyone the right, and perhaps one of the most jurisprudential doors to take care of the door of inheritance and wills, has been contained verses Koranic and prophetic sayings so as not to get a conflict between Muslims, has developed in this era a new regime has to do And the inheritance of the grandfather and their uncles shall take the entire inheritance. These grandchildren shall remain poor, while their father, if he were alive, would have been left with the inheritance of the father. Has a share of inheritance, which is taken by the law of families Algerian government after 1984, and there was disagreement and debate in the adaptation of the legitimacy, and then after the judgment, and asked through this research to reveal the truth and ruling in Islamic law
مقال بمجلة الشهاب
Keywords: التنزيل – الوصية - الواجبة – ميراث – الحفدة – قانون الأسرة